EXPLICIT COMPARISONS IN DEVELOPING INTERCULTURAL COMPETENCE - Indawan Syahri (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
Since English is claimed as lingua franca among nations, interculturalcompetence (ICC, henceforth) becomes a new enterprise in EnglishLanguage Teaching (ELT). The teaching of English should putforward to capturing target culture, but unnecessarily neglect thelocal culture. It should embed not only the target culture, but alsoother non-native cultures of periphery nations. Responding to theemergence of non-native varieties of English and to the fact that peoplefrom non-native countries of English communicate in English,teaching-learning materials and activities should also cover the nonnativecultures of English. This paper attempts to offer an alternativemode to develop the learners’ ICC. The explicit comparisons, then,consequently comprise both cultures, i.e., learners’ cultures andcultures applied by other non-native speakers. Emphasizing ondeveloping learners’ ICC seems more promising than those ofdeveloping communicative competence (CC), though it is hard to putinto practice.